2020
DOI: 10.1002/hed.26328
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of racial survival disparities among oropharyngeal cancer cases by HPV status

Abstract: Background There is a well documented racial disparity in overall survival for oropharyngeal squamous cell carcinoma (OPSCC); however, it is unknown to what extent this disparity varies by HPV‐status. Methods A literature search was conducted through December 2019 using Ovid Medline, Cochrane Library, Embase, Scopus, and http://Clinicaltrials.gov. PRISMA guidelines were followed. A meta‐analysis was conducted using random effects models to obtain pooled hazard ratios (HRs). Results Of 649 studies initially ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Another study of patients with sinonasal undifferentiated carcinoma reported significantly worse overall survival outcomes in patients with government insurance or low education 21 . Based on these findings, as well as findings from other studies reported in head and neck oncology literature, 22–24 it is plausible that low socioeconomic status might drive the racial disparity observed in our sample. A notable limitation of our retrospective analysis is that our dataset lacked information on household income, education, or insurance status.…”
Section: Discussionsupporting
confidence: 73%
“…Another study of patients with sinonasal undifferentiated carcinoma reported significantly worse overall survival outcomes in patients with government insurance or low education 21 . Based on these findings, as well as findings from other studies reported in head and neck oncology literature, 22–24 it is plausible that low socioeconomic status might drive the racial disparity observed in our sample. A notable limitation of our retrospective analysis is that our dataset lacked information on household income, education, or insurance status.…”
Section: Discussionsupporting
confidence: 73%
“…Guidelines have recommended that all OPC patients should be tested for HPV status and HPV-positive OPC was specified separately as an independent entity in the eighth edition of the American Joint Committee on Cancer (AJCC) tumor node metastasis (TNM) staging system (11)(12)(13). OPC patients with HPV positivity showed an improved response to therapy and a better survival (14,15). However, the role of HPV infection in non-oropharyngeal HNSCC of the nasopharynx, oral cavity, and hypopharynx was not well defined despite HPV infection being present in 7% to 25% of non-oropharyngeal HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, black patients have worse survival outcomes, even after adjusting for disease stage (including untreatable disease), and treatment factors 12 . A recent meta‐analysis of survival disparities in squamous cell oropharyngeal cancer demonstrated a trend toward poorer survival in black patients with HPV‐negative tumors 13 . The mediators of the persistent racial disparities in oropharyngeal carcinoma are not well understood; however, further elucidation of these mediators can help identify actionable targets for interventions aimed at addressing disparities.…”
Section: Introductionmentioning
confidence: 99%